Pembangkitan Kunci pada Algoritma Hill Cipher menggunakan Teknik Distribusi Angka Diffie-Hellman - Andysah Putera Utama Siahaan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Sending data needs to be done properly and safely because it involves important information owned by a person, company or certain party. Sending messages often uses passwords or keywords so that the sending process goes well. The recipient of the message must have the password to be able to open the message after it is received. The key exchange causes the key to be known by irresponsible parties. The key generation process using the Diffie-Hellman algorithm is a good technique to avoid key exchange between sender and receiver. This study uses the Hill Cipher algorithm to test the generation of four keys which will be placed in a 2 x 2 key matrix. As a result, each key that will be generated will use the Diffie-Hellman technique in determining the value to be entered into the Hill Cipher key matrix. The use of this technique is very well done in providing the Hill Cipher algorithm key to the recipient of the message so that it can open the message sent by the sender.